1991
DOI: 10.1063/1.460006
|View full text |Cite
|
Sign up to set email alerts
|

Small-angle x-ray scattering from the surfaces of reversed-phase silicas: Power-law scattering exponents of magnitudes greater than four

Abstract: The small-angle x-ray scattering from fully and partially derivatized porous silicas has been studied. Power-law-scattering exponents of magnitude greater than 4 have been found in all cases. The magnitudes of the exponents increased with the alkyl chain length and with the degree of surface derivatization. In a preliminary model to explain these observations, a power-law-scattering exponent with magnitude greater than 4 is related to a ‘‘fuzzy’’ pore boundary, in which the density varies continuously at the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
80
0
2

Year Published

1991
1991
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(85 citation statements)
references
References 12 publications
3
80
0
2
Order By: Relevance
“…The non-homogeneity of these particles is determined by their interface conventionally defined here as a "diffusive surface". It is close to the concept introduced by Schmidt (Schmidt, 1995) of a diffusive interface between two homogeneous phases to explain the experimentally observed deviations of the scattering from the Porod law towards lower values of the power-law exponent (< 4) at large qvalues in reversed-phase silicas (Schmidt et al, 1991b). The same deviations were revealed for SANS from ethanol solutions of hydrolyzed TEOS (Avdeev et al, 2004).…”
Section: Introductionsupporting
confidence: 62%
“…The non-homogeneity of these particles is determined by their interface conventionally defined here as a "diffusive surface". It is close to the concept introduced by Schmidt (Schmidt, 1995) of a diffusive interface between two homogeneous phases to explain the experimentally observed deviations of the scattering from the Porod law towards lower values of the power-law exponent (< 4) at large qvalues in reversed-phase silicas (Schmidt et al, 1991b). The same deviations were revealed for SANS from ethanol solutions of hydrolyzed TEOS (Avdeev et al, 2004).…”
Section: Introductionsupporting
confidence: 62%
“…In this section I discuss the application of (16) and (17) in an investigation (Schmidt et at., 1991) of porous silicas in which hydrocarbon molecules had been attached to the pore surfaces. These silicas, which are often called reversed-phase silicas, have many important applications in chromatography.…”
Section: Power-law Scattering With Exponents Of Magnitude Greater Thamentioning
confidence: 99%
“…For points on the bound- ary surface, x = 0 and positive values of x specify points in the solid. The scattered intensity for this model is given by the equation (Schmidt et al, 1991) …”
Section: Power-law Scattering From Non-fractal Scatterersmentioning
confidence: 99%
See 1 more Smart Citation
“…The N 2 -gas adsorption method has been widely used to measure the specific surface area (SSA) and characterize the open porosity of airdried soil particles, especially the mesoporosity (pore width between 2-50 nm) and microporosity (pore width not exceeding 2 nm) (Mayer et al, 2004;Pronk et al, 2011). The small-angle X-ray scattering (SAXS) technique (Guinier and Fournet, 1955) has been used more generally for the internal and external structural characterization of porous solid materials on a length scale of typically 1 nm to 100 nm as in the case of silica gel (Schmidt, 1991;Schmidt et al, 1991) and clay minerals (Pernyeszi and Dékány, 2003). It has been shown that SAXS technique is suitable for studying fractal dimensions, (D) of powders with porous or irregular surface (Höhr et al, 1988;Schmidt, 1991) where D values are provided from a power law of the measured scattered intensity I(q) as a function of the scattering angle 2θ.…”
Section: Introductionmentioning
confidence: 99%